Concurrent validation of the OMNI perceived exertion scale for resistance exercise - Robertson, R. J.; Goss, F. L.; Rutkowski, J.; Lenz, B.; Dixon, C.; Timmer, J.; Frazee, K.; Dube, J.; Andreacci, J. (Medicine & Science in Sports & Exercise, 2011)
Purpose: Concurrent validity of the newly developed OMNI-Resistance Exercise Scale (OMNI-RES) of perceived exertion was examined for 18- to 30-yr-old women (N = 20) and men (N = 20) performing biceps curl (BC) and knee extension (KE) exercise.